Selected poetry of Emily Dickinson - Dickinson, Emily 1830-1886 (Collector's edition / New York Public Library, 1997)
Virtually unpublished in her lifetime and unknown at her death in 1886, Emily Dickinson stands today in the front rank of American poets. Though she lived as a recluse in her father's house in Amherst, Massachusetts, her imagination knew no bounds, ranging with utter fearlessness through a vast landscape of love, immortality, nature, joy, faith, and despair. After Dickinson's death, her sister Vinnie was stunned to discover a locked box containing over nine hundred poems - an extraordinary body of work which the poet considered her "letter to the world." This edition gathers a rich harvest of the finest of these poems, carefully selected by the staff of The New York Public Library. Arranged chronologically, they chart the development of a poetic sensibility fired by immediacy of perception and a magnificent grasp of language. Emily Dickinson and her world are further evoked here with rare manuscripts and prints drawn from the Library's special collections, including a selection of the poet's handwritten letters.